Strategy for fostering the maluku and papua shariah cooperative to become an alternative financial institution - Nuryadi Saputra, Asep; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2016)
Abstract - In latest three years, Indonesia’s economic perform tended to decrease. It’s because of the global financial crisis which impact to global economic performance. But practically, Indonesia’s economic decreased should not affected to financial institutions perform specially Shariah financial institutions. Its reflected from financial report of Shariah Bank and Shariah Rural Bank, both of them perform are increased significantly in the year of 2013 but in the year of 2014’s their financial perform are decreased. Nevertheless Shariah Cooperative perform are decreased but it still generated good profit.However, the good perform of Shariah Cooperative are represent some of cooperative perform. Those symptom leaded this research to find the problem of Maluku and Papua’s Shariah Cooperative. To solve the problem, formulationstrategy begin with internal assessment using VRINE and Value Chain Analysis. Further, external were using PEST and Porter’s 5 Forces Analysis. Those assessment were summarized in SWOT and GE Matrix to analyze their position. The resultwere in quadrant five which is maintain and hold position with average to strong competitive position meanwhile market attractiveness were medium to high. With selective or manage for earning strategy, Maluku and Papua’s Shariah Cooperative were recommended to protect existing program, focus to market segment and tried to make a partnership with reputable Shariah Bank. Keywords: Shariah Cooperative, Maluku Papua, SWOT, GE Matrix, Developing Strategy